Management Audit as a Basis to Assess the Efficiency and Effectiveness of Marketing Function at the Inaya Putri Bali Hotel - I Gusti Ngurah Satya Dharma; I B A Yasa; A A P Suardani (Jurusan Akuntansi Politeknik Negeri Bali, 2020)
This study aims to assess the efficiency and effectiveness of the implementation of the marketing function at the Inaya Putri Bali Hotel and reveal the findings obtained during the management audit. Based on findings audit, it can be given right recommendations to make company's future performance better. The data analysis techniques used are quantitative and qualitative methods. Data used is sourced from primary and secondary data through interviews, observations, and documentation. The research begins with collection of data and information relevant to marketing function then processed and analyzed in conformity with the company's plans and guidelines as well as calculation of effectiveness and efficiency levels of Revenue and marketing costs. The results of this research show efficiency of marketing function in Inaya Putri Bali Hotel runs efficiently, but effectiveness marketing function is still under standards company caused by decrease in income room, food and beverage. The company needs to evaluate all sales and marketing management staff, make an innovative promotion programs, make all sales personel to be active to attend exhibition,sales mission also hotel events and provide training to sales personnel periodically to support performance Inaya Putri Bali Hotel in maximizing the income of room, food and beverage for company.